Cardiac to cancer: Connecting connexins to clinical opportunity. Issue 8 (4th March 2014) - Grek, Christina L.; Rhett, J. Matthew; Ghatnekar, Gautam S.
Abstract : Gap junctions and their connexin components are indispensable in mediating the cellular coordination required for tissue and organ homeostasis. The critical nature of their existence mandates a connection to disease while at the same time offering therapeutic potential. Therapeutic intervention may be offered through the pharmacological and molecular disruption of the pathways involved in connexin biosynthesis, gap junction assembly, stabilization, or degradation. Chemical inhibitors aimed at closing connexin channels, peptide mimetics corresponding to short connexin sequences, and gene therapy approaches have been incredibly useful molecular tools in deciphering the complexities associated with connexin biology. Recently, therapeutic potential in targeting connexins has evolved from basic research in cell‐based models to clinical opportunity in the form of human trials. Clinical promise is particularly evident with regards to targeting connexin43 in the context of wound healing. The following review is aimed at highlighting novel advances where the pharmacological manipulation of connexin biology has proven beneficial in animals or humans.